2019
DOI: 10.1111/iju.13946
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict vesicoureteral reflux resolution in patients with non‐neurogenic lower urinary tract dysfunction?

Abstract: Objective To analyze factors influencing reflux resolution in patients with the coexistence of non‐neurogenic lower urinary tract dysfunction and vesicoureteral reflux. Methods The data of 153 children who were diagnosed with vesicoureteral reflux and accompanying non‐neurogenic lower urinary tract dysfunction between 2010 and 2015 were retrospectively evaluated. Patients with neurogenic and anatomical malformations, monosymptomatic nocturnal enuresis, previous history of vesicoureteral reflux surgery, irregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Guney et al studied 122 surgically managed children by ureteral reimplantation for VUR and identified a rate of redo reimplantation of 8% among patients but failed to find any factor correlating with the initial reimplantation failure [4]. An interesting study did find that the absence of high PVR in these children significantly correlated with a higher resolution rate of VUR [5]. Another study found that PVR was the single factor correlating with the prognosis of management of VUR [6].…”
Section: Introductionmentioning
confidence: 99%
“…Guney et al studied 122 surgically managed children by ureteral reimplantation for VUR and identified a rate of redo reimplantation of 8% among patients but failed to find any factor correlating with the initial reimplantation failure [4]. An interesting study did find that the absence of high PVR in these children significantly correlated with a higher resolution rate of VUR [5]. Another study found that PVR was the single factor correlating with the prognosis of management of VUR [6].…”
Section: Introductionmentioning
confidence: 99%